Pentingnya Gaya Kepemimpinan Dalam Perilaku Organisasi - Christie, Angelia; Fauzi, Achmad; Harahap, Abdul Halim; Difa andani, Claresta; Nurhaliza, Divtyajeng (Green Publisher, 2023)
A leader is considered to have a major role to provide direction and influence organizational behavior. In an organization must have people who can organize and provide direction so that an organization can move as it should as well as possible. Therefore the figure of a leader is needed in an organization because all decisions, movements and the pace of progress of a company depend on the mindset and goals of a leader. Leaders are considered as agents of change, where they are individuals who accelerate the pace of the organization and influence the actions of other individuals in the organization. This study aims to explore how important the actions taken by a leader in influencing a performance in an organization. In this study we used a qualitative method by utilizing social media, namely Tiktok, Youtube and Instagram as objects of leadership in a company